(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2024)
The set of didactic proposals that we present are the result of the teachers training course ‘Entrance doors to the study of railways in Argentina. Between progress, development, deficit and heritage’ that we dictate in the Union of teachers and researchers of the National University of Rosario, Santa Fe, Argentina. We were encouraged by the intention of offering topics and problems that can be addressed in the classrooms and related to general contents of the official curriculum that the Ministry of Education of the Province of Santa Fe establishes as mandatory for the subjects History, Geography and those related to social sciences for secondary school. The participants were teachers (at different levels of the educational system) and students, from tertiary institutes and universities.